Energy-Adjusted Dietary Inflammatory Index Is Associated With 5-Year All Cause and Cardiovascular Mortality Among Chronic Kidney Disease Patients - Huang, Ying; Zhang, Lei; Zeng, Mengru; Liu, Fuyou; Sun, Lin; Liu, Yu; Xiao, Li (Frontiers in Nutrition, 2022)
Background: Diet management is a pivotal intervention for chronic kidney disease (CKD) patients. Dietary inflammation index (DII) is developed to evaluate the integral inflammatory potential of a diet pattern. However, research about the association between DII and mortality in CKD is limited. Objective: We conducted a cohort study to investigate the relationship between energy adjusted DII (E-DII) and the 5-year all-cause and cardiovascular mortality in CKD population. Materials and Methods: CKD participants with complete E-DII data and death status from National Health and Nutrition Examination Survey (1999-2014) were involved in this study. E-DII was calculated based on dietary recall interviews. Smooth curve fitting, Kaplan–Meier survival analysis and Cox proportional hazards models were used to evaluate the association between E-DII and the 5-year all cause and cardiovascular mortality. Subgroup analysis was also performed. Results: 7207 participants were included (55.46% elderly and 46.54% male) in this study. The 5-year all-cause and cardiovascular mortality were 16.86% and 4.32%, respectively. Smooth curve fitting showed a “J” shape and near linear relationship between the E-DII score and the 5-year all-cause and cardiovascular mortality, respectively. In multivariate Cox proportional hazards models, the hazard ratios (95% confidence intervals) for the highest tertile of the E-DII were 1.33 (1.15, 1.54) for all-cause mortality, and 1.54 (1.15, 2.07) for cardiovascular mortality when compared with the lowest tertile of the E-DII. Subgroup analyses revealed relatively stronger associations between the E-DII and the mortality among CKD patients with other death risk factors. Conclusions: Energy adjusted dietary inflammatory index is independently related with the 5-year all-cause and cardiovascular mortality among CKD patients. Therefore, anti-inflammatory diet patterns should be recommended for CKD patients.